Development of biometric recognition system using electroencephalogram (EEG) signals - Ericsen (2017)
As the technology advancing at phenomenal rate, security had become an integral part of life. Regardless of whether it is a personal, business security or government security, security becomes an important issue which requiring constant upgrading. Biometric recognition system had been deployed widely; however, the security risk for the biometric system had grown significantly. Hence, there is a need to find more biological traits which are more secure against potential security attack. As of recent, there had been much research on the electroencephalogram signals as a new modality that can be used to develop a more robust biometric system due to its uniqueness and its robustness against the threat. This report will present the use of EEG as a potential biometric system with the use of self and relatives’ image.